Themes of exile in the poetry and prose of Ezra Pound in The New Age - Simmons, Samuel James Elijah (The University of Edinburgh, 2009)
The current study offers an analysis of the American poet Ezra Pound and his years in London between 1908 and 1921, specifically those years when he contributed to A.R. Orage's The New Age. Despite the volume of critical work on Pound, and despite the wealth of his writings in The New Age, this body of work has not previously received the attention of a full-length study.

Chapter One of this thesis sets the stage for Pound's emergence as critic of cultural modernity by exploring a key theme that resonates throughout his contributions to The New Age: the idea of the modern artist as exile. This chapter also examines the importance of the idea of translation to his thought during this period and presents a broader analysis of the economic and literary importance of The New Age to his intellectual and aesthetic development. Chapter Two broadens this analysis by examining the themes of personal exile and psychological isolation in Pound's historical background and the effect these themes had upon his writing for The New Age. Chapters Three and Four examine two key ideas that animate his work for The New Age: his analysis of the importance of patronage to cultural value and aesthetic production and his developing interest in economics, C.H. Douglas' Economic Democracy and its doctrine of Social Credit. Chapters Five and Six explore Pound's literary relationship to The New Age in order to discuss how this nexus of ideas inflect two of his early masterpieces, 'The Seafarer'(1911) and 'Homage to Sextus Propertius' (1919). Chapter Seven concludes by summarising Pound's position at the end of the 1920s and considering the overall importance of his writing for The New Age to his social critique of modernity, his emerging economic radicalism and his later political ideas.